CAD and GIS integration - Karimi, Hassan A.; Akinci, Burcu (Boca Raton, FL. : CRC Press, 2010)
'From early developments to current trends and future directions, this concise resource allows you to get up to speed quickly on what it takes to get the most from these two dynamic technologies. Numerous example applications of effective CAD/GIS integration provide the understanding needed to improve designs, make better decisions, and reduce or even eliminate costly errors in your next project.'--BOOK JACKET.
'An Auerbach book.'
Includes bibliographical references and index.
Keywords: Geographic information systems -- Computer-aided design; Geography -- Mathematical models -- Computer-aided design; Software compatibility